Single-Step Self-Assembly of Zein-Honey-Chitosan Nanoparticles for Hydrophilic Drug Incorporation by Flash Nanoprecipitation - Jorge Loureiro; Sónia P. Miguel; Inês J. Seabra; Maximiano P. Ribeiro; Paula Coutinho (MDPI AG, 2022)
Zein- and chitosan-based nanoparticles have been described as promising carrier systems for food, biomedical and pharmaceutical applications. However, the manufacture of size-controlled zein and chitosan particles is challenging. In this study, an adapted anti-solvent nanoprecipitation method was developed. The effects of the concentration of zein and chitosan and the pH of the collection solution on the properties of the zein-honey-chitosan nanoparticles were investigated. Flash nanoprecipitation was demonstrated as a rapid, scalable, single-step method to achieve the self-assembly of zein-honey-chitosan nanoparticles. The nanoparticles size was tuned by varying certain formulation parameters, including the total concentration and ratio of the polymers. The zein-honey-chitosan nanoparticles' hydrodynamic diameter was below 200 nm and the particles were stable for 30 days. Vitamin C was used as a hydrophilic model substance and efficiently encapsulated into these nanoparticles. This study opens a promising pathway for one-step producing zein-honey-chitosan nanoparticles by flash nanoprecipitation for hydrophilic compounds' encapsulation.